Implementation Of Ratcliff/Obershelp And Cosine Similarity Methods On Image For Detection - Lianda, Deri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Image is a tool for communicating in conveying certain messages from the image maker, so that images can be used as language in the technical field. Important pictures are stored by the user on a storage medium. The problem that occurs is that an image can be copied for personal gain, for example forging scanned images on important documents that can be misused. This study uses the Ratcliff/Obershelp and Cosine Similarity methods to detect similarities and differences in image images. So that with the implementation of the Ratcliff/Obershelp and Cosine Similarity methods for detecting similarities and differences in images, the image similarities can be known.